Emotion Dysregulation as a Cause of Eating Disorder: A Literature Review - Gea Nina Agasta Basmalah; Ashfa Zahidah Amani; Nacjwa Alifia Annabila; Damajanti Kusuma Dewi (International Conference on Psychology and Education (ICPE), 2025)
This study aims to examine the relationship between emotion dysregulation as a cause of eating disorders based on research articles that have been collected. The method used was systematic review by collecting and analyzing various research articles relevant to the research objectives. Based on the results of the 18 articles analyzed, it can be concluded that difficulty regulating emotions plays an important role in the emergence and perpetuation of eating disorders, especially binge eating disorder (BED). Emotion dysregulation also serves as a mediator in relation to eating disorders. Thus, interventions that emphasize the development of emotion management skills may be an important strategy in preventing and managing eating disorders.